Prognostic implications of baseline and new-onset fragmented qrs complex in patients undergoing transcatheter aortic valve implantation - Hakgör, Aykun; Dursun, Atakan; Akhundova, Aysel; Kenger, Melike Zeynep; Savur, Ümeyir; Derviş, Emir; Çeleğen, Muhammed Furkan; Boztosun, Bilal (My University, 2024)
Fragmented QRS complex (fQRS), which can be easily detected by electrocardiography (ECG), is an indicator of myocardial fibrosis and has adverse prognostic impact in cardiovascular diseases. The aim of this study was to investigate the effect of the presence of both pre-and post-operative fQRS on short-and long-term prognosis in patients undergoing transcatheter aortic valve implantation (TAVI) for severe aortic stenosis (AS). Data of 615 patients who underwent TAVI from different risk categories in a single-center were retrospectively screened and 289 patients were included after exclusion criteria. The presence of fQRS was recorded on pre-and postoperative ECGs and the effect of the fQRS on in-hospital and 2-year all-cause mortality was investigated. fQRS was detected in 85 (29.4%) patients before TAVI and also 24 (11.8%) patients had new-onset fQRS after TAVI. The presence of preop fQRS was found to be an independent predictor of in-hospital mortality. Postop fQRS, moderate or severe paravalvular aortic regurgitation and high systolic pulmonary artery pressure were associated with long-term mortality. In addition, patients with preop fQRS were more likely to need permanent pacemaker implantation after TAVI (14.1% vs. 2.9%). fQRS, which can be considered an indicator of subclinical left ventricular dysfunction due to myocardial fibrosis, is associated with decreased short-and long-term survival in patients undergoing TAVI. The presence of preop fQRS and postop new-onset fQRS is associated with a 3.8-and 3.2-fold increased cumulative mortality risk, respectively, at 24-month follow-up compared to patients without fQRS.
Keywords: Aortic Stenosis; Electrocardiogram; Fragmented QRS Complex; Long-Term Outcomes; Transcatheter Aortic Valve Implantation